Optimal. Leaf size=29 \[ 3+x-\frac {x^3}{x+\frac {1}{3} \left (-5-e^x+e^{2 x}+x\right )} \]
________________________________________________________________________________________
Rubi [F] time = 1.52, antiderivative size = 0, normalized size of antiderivative = 0.00, number of steps used = 0, number of rules used = 0, integrand size = 0, \(\frac {\text {number of rules}}{\text {integrand size}}\) = 0.000, Rules used = {} \begin {gather*} \int \frac {25+e^{2 x}+e^{4 x}-40 x+61 x^2-24 x^3+e^x \left (10-8 x+9 x^2-3 x^3\right )+e^{2 x} \left (-10-2 e^x+8 x-9 x^2+6 x^3\right )}{25+e^{2 x}+e^{4 x}+e^x (10-8 x)-40 x+16 x^2+e^{2 x} \left (-10-2 e^x+8 x\right )} \, dx \end {gather*}
Verification is not applicable to the result.
[In]
[Out]
Rubi steps
\begin {gather*} \begin {aligned} \text {integral} &=\int \frac {25-2 e^{3 x}+e^{4 x}-40 x+61 x^2-24 x^3+e^x \left (10-8 x+9 x^2-3 x^3\right )+e^{2 x} \left (-9+8 x-9 x^2+6 x^3\right )}{\left (5+e^x-e^{2 x}-4 x\right )^2} \, dx\\ &=\int \left (1+\frac {3 \left (14+e^x-8 x\right ) x^3}{\left (-5-e^x+e^{2 x}+4 x\right )^2}+\frac {3 x^2 (-3+2 x)}{-5-e^x+e^{2 x}+4 x}\right ) \, dx\\ &=x+3 \int \frac {\left (14+e^x-8 x\right ) x^3}{\left (-5-e^x+e^{2 x}+4 x\right )^2} \, dx+3 \int \frac {x^2 (-3+2 x)}{-5-e^x+e^{2 x}+4 x} \, dx\\ &=x+3 \int \left (\frac {14 x^3}{\left (-5-e^x+e^{2 x}+4 x\right )^2}+\frac {e^x x^3}{\left (-5-e^x+e^{2 x}+4 x\right )^2}-\frac {8 x^4}{\left (-5-e^x+e^{2 x}+4 x\right )^2}\right ) \, dx+3 \int \left (-\frac {3 x^2}{-5-e^x+e^{2 x}+4 x}+\frac {2 x^3}{-5-e^x+e^{2 x}+4 x}\right ) \, dx\\ &=x+3 \int \frac {e^x x^3}{\left (-5-e^x+e^{2 x}+4 x\right )^2} \, dx+6 \int \frac {x^3}{-5-e^x+e^{2 x}+4 x} \, dx-9 \int \frac {x^2}{-5-e^x+e^{2 x}+4 x} \, dx-24 \int \frac {x^4}{\left (-5-e^x+e^{2 x}+4 x\right )^2} \, dx+42 \int \frac {x^3}{\left (-5-e^x+e^{2 x}+4 x\right )^2} \, dx\\ \end {aligned} \end {gather*}
________________________________________________________________________________________
Mathematica [A] time = 0.05, size = 24, normalized size = 0.83 \begin {gather*} x-\frac {3 x^3}{-5-e^x+e^{2 x}+4 x} \end {gather*}
Antiderivative was successfully verified.
[In]
[Out]
________________________________________________________________________________________
fricas [A] time = 0.57, size = 42, normalized size = 1.45 \begin {gather*} -\frac {3 \, x^{3} - 4 \, x^{2} - x e^{\left (2 \, x\right )} + x e^{x} + 5 \, x}{4 \, x + e^{\left (2 \, x\right )} - e^{x} - 5} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
giac [A] time = 0.24, size = 42, normalized size = 1.45 \begin {gather*} -\frac {6 \, x^{3} - 4 \, x^{2} - x e^{\left (2 \, x\right )} + x e^{x} + 5 \, x}{4 \, x + e^{\left (2 \, x\right )} - e^{x} - 5} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
maple [A] time = 0.08, size = 23, normalized size = 0.79
method | result | size |
risch | \(x -\frac {3 x^{3}}{4 x -5+{\mathrm e}^{2 x}-{\mathrm e}^{x}}\) | \(23\) |
norman | \(\frac {x \,{\mathrm e}^{2 x}-\frac {5 \,{\mathrm e}^{x}}{4}+\frac {5 \,{\mathrm e}^{2 x}}{4}+4 x^{2}-3 x^{3}-{\mathrm e}^{x} x -\frac {25}{4}}{4 x -5+{\mathrm e}^{2 x}-{\mathrm e}^{x}}\) | \(50\) |
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
maxima [A] time = 0.70, size = 42, normalized size = 1.45 \begin {gather*} -\frac {3 \, x^{3} - 4 \, x^{2} - x e^{\left (2 \, x\right )} + x e^{x} + 5 \, x}{4 \, x + e^{\left (2 \, x\right )} - e^{x} - 5} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
mupad [B] time = 2.38, size = 22, normalized size = 0.76 \begin {gather*} x-\frac {3\,x^3}{4\,x+{\mathrm {e}}^{2\,x}-{\mathrm {e}}^x-5} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
sympy [A] time = 0.16, size = 19, normalized size = 0.66 \begin {gather*} - \frac {3 x^{3}}{4 x + e^{2 x} - e^{x} - 5} + x \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________